The Role of Social Media in Enhancing Digital Literacy Among Generation Z: A Social and Psychological Perspective - Siti Maisuroh; Moh. Jamil; Umar Manshur (Journal of Social Studies and Education, 2024)
This research explores the role of social media and digital education programs in improving Generation Z's digital literacy, including critical thinking, information evaluation and social skills. The research method used a qualitative case study approach, with secondary school students in Probolinggo Regency as the unit of analysis. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using data reduction, presentation, and verification to produce in-depth and holistic findings. The results showed that students who actively use social media, such as TikTok, Instagram and YouTube, have a better ability to evaluate information than those who are less active. Interactive app-based digital education programs such as Kahoot and Google Classroom are proven to improve students' learning motivation and critical thinking skills. In addition, collaborative learning positively contributes to the development of social skills, such as communication and cooperation. The findings confirm the importance of integrating social media, learning technology and collaborative approaches to create a more relevant and adaptive learning environment in the digital era. This research provides theoretical and practical contributions in the development of effective technology-based education strategies for Generation Z. Support from teachers, parents and education stakeholders is needed to maximize the positive impact of technology. It also opens up further exploration of demographic factors, such as gender and age, and the long-term impact of social media on education.